EFISIENSI KOMUNIKASI PEMANDU LALU LINTAS PENERBANGAN DENGAN UNIT PERTAMINA DAN PKP-PK PASCA ADANYA AKSES JALAN DI BANDAR UDARA AJI PANGERAN TUMENGGUNG PRANOTO SAMARINDA - Erlangga, Rendra; Amir, Elfi (Jurnal Penelitian, 2024)
This research was conducted at Aji Pangeran Tumenggung Pranoto International Airport in Samarinda to determine the efficiency of communication after road access which affects flight safety. The method used in this research is descriptive qualitative. The data collection technique used was a documentation study and direct observation in the field from December 2020 to February 2021. The results showed that the movement of Pertamina and PKP-PK unit vehicles in the manouevering area and movement area of Aji Pangeran Tumenggung Pranoto Samarinda International Airport often impeded movement aircraft. There is a need for access road to improve flight safety and reduce the load of communication between air traffic controllers and the Pertamina and PKP-PK units at Aji Pangeran Tumenggung Pranoto International Airport, Samarinda.